Infant and Young Child Feeding Practices: A Cross-Sectional Study amongst Mothers in the Urban Field Practice Area of Navodaya Medical College, Raichur - Kusuma Achalkar; Bheemayya Badesab (Medsci Publications, 2019)
Background: Malnutrition is one of the commonest causes underly- ing under five mortality in developing countries like India. The first two years after birth of child is the critical window period for pro- motion of good growth, health, behavioural and cognitive develop- ment. The research aimed to study the current practices of infant and young child feeding among mothers and socio-demographic factors influencing it. Methodology: A cross-sectional study was conducted in the urban area among 375 mothers having children of less than two years. Data was collected after informed consent regarding socio-demo- graphic factors and child feeding practices from mothers. Data was analyzed using EPI Info 7 and expressed in terms of percentages, proportions and chi-square value. Results: In our study 46.7% children of less than two years were exclusively breastfed for 6 months. 17.3% of children were fed with complementary foods at 6 months of age. The study showed 35.5% of children had minimum diet diversity and 50.85% were given minimum meal frequency. Mothers' education was found to be significantly associated with child feeding practices. Conclusion: In our study Infant and young child feeding (IYCF) practices were much less. The study shows giving importance to fe- male literacy, improving socioeconomic condition of mothers in the community will bring greater changes in the practice of  optimal IYCF practices.